Rural E-commerce Development Mode and Promotion Path Exploration - Ge, Yunxian (Journal of Theory and Practice of Social Science, 2023)
The development of the information age has promoted the continuous progress in the field of e-commerce, now e-commerce in rural areas has also achieved very outstanding results, only the development of e-commerce in rural areas has made a major breakthrough, in order to promote the overall progress in the field of e-commerce. Therefore, relevant departments should pay more attention to take diversified effective measures to achieve sustainable development in the field of e-commerce. The sustainable development of rural e-commerce helps more and more users get rid of the hat of poverty. In order to effectively integrate the basic concept of modernization into the field of e-commerce, effectively promote the implementation of the rural revitalization strategy to achieve the next promotion of economic development, it is necessary to enhance the development of rural e-commerce innovation. To achieve the transformation of economic model to ensure that e-commerce can bring a positive impact on the development of rural areas, to achieve the equipment goal of common prosperity and common development. This paper mainly analyzes the problems of rural e-commerce development, the overall situation of the current rural e-commerce development, the importance of developing rural e-commerce, and the effective strategies to promote the progress of rural e-commerce.